Analysis of gene expression profiles between apical papilla tissues, stem cells from apical papilla and cell sheet to identify the key modulators in MSCs niche. (1st February 2017) - Diao, Shu; Lin, Xiao; Wang, Liping; Dong, Rui; Du, Juan; Yang, Dongmei; Fan, Zhipeng
Abstract: Objectives: The microenvironmental niche plays the key role for maintaining the cell functions. The stem cells from apical papilla (SCAPs) are important for tooth development and regeneration. However, there is limited knowledge about the key factors in niche for maintaining the function of SCAPs. In this study, we analyse the gene expression profiles between apical papilla tissues, SCAPs and SCAPs cell sheet to identify the key genes in SCAPs niche. Materials and methods: Microarray assays and bioinformatic analysis were performed to screen the differential genes between apical papilla tissues and SCAPs, and SCAPs and SCAPs cell sheet. Recombinant human BMP6 protein was used in SCAPs. Then CCK‐8 assay, CFSE assay, alkaline phosphatase activity, alizarin red staining, quantitative calcium analysis and real‐time reverse transcriptase‐polymerase chain reaction were performed to investigate the cell proliferation and differentiation potentials of SCAPs. Results: Microarray analysis found that 846 genes were up‐regulated and 1203 genes were down‐regulated in SCAPs compared with apical papilla tissues. While 240 genes were up‐regulated and 50 genes were down‐regulated in SCAPs compared to in SCAPs cell sheet. Moreover, only 31 gene expressions in apical papilla tissues were recovered in cell sheet compared with SCAPs. Bioinformatic analysis identified that TGF‐β, WNT and MAPK signalling pathways may play an important role in SCAPs niche. Based on the analysis, we identified one key growth factor in niche, BMP6, which could enhance the cell proliferation, the osteo/dentinogenic, neurogenic and angiogenic differentiation potentials of SCAPs. Conclusions: Our results provided insight into the mechanisms of the microenvironmental niche which regulate the function of SCAPs, and identified the key candidate genes in niche to promote mesenchymal stem cells‐mediated dental tissue regeneration.